Biosyngas-fueled platinum reactor applied in micro combined heat and power system with a thermophotovoltaic array and stirling engine. (1st March 2020) - Chen, Wen-Lih; Huang, Chao-Wei; Li, Yueh-Heng; Kao, Chien-Chun; Cong, Huynh Thanh
Abstract: Currently, alternative fuels, derived from biomass and urban maximize the overall power output, have been increasingly attracting more attention in the industrial and residential sectors. Micro-combined heat and power (CHP) systems with high energy efficiency have been developed, particularly for the use in remote and rural areas. This study used a micro-CHP system, with a combustion-driven thermophotovoltaic (TPV) cell array and a Stirling engine-driven power system, within which methane and bio-syngas fuels were deployed strategically. This micro-CHP system harvests energy generated through thermal radiation from the reactor surface and harvests thermal energy from hot flue gas. Eventually, the micro-CHP prototype was proven that all energies are converted to electricity, and hot water can be simultaneously supplied. High incandescent surface and high-temperature flue gas of platinum reactor provide the thermal sources for TPV cell array and Stirling engine. The overall efficiency of the micro-CHP system was 35.0% for 50%H2 +50%CO, and the generated power included 2.7, 3.5, and 272.1 W from the Stirling engine-driven power system, GaSb TPV cell array, and hot water supply system, respectively. The systematic performance of the micro-CHP system, the combustion features, radiation efficiency, fuel conversion rate, total electricity output, and corresponding overall efficiencies were examined thoroughly. Highlights: Micro-combined heat and power (CHP) system fueled with biosyngas was developed. The micro-CHP system comprises the PV array and Stirling engine power system. The platinum combustor mitigates fuel variability and flame instability. The overall efficiencies of the micro-CHP are assessed under various conditions.